Altitude training
This fourth issue of Volume 2 of Coaching Science Abstracts reviews 33 articles concerned with altitude training. It includes some discussion of responses which constitute altitude acclimatization and the effects of altitude exposure and acclimatization on performance. The articles are divides into the following topics: - ALTITUDE ADAPTATION and - LIVE HIGH -- TRAIN LOW. (You can look at the articles also seperately from the mainpage on.)